ANALYSIS OF ALTERNATIVE SOCIAL PROTECTION POLICIES IN INDONESIA: A SYSTEMATIC REVIEW OF RESILIENCE, DIGITALIZATION, AND GOVERNANCE (2020-2025) - Tb. Ace Hasan Syadzily; Ade Sofyan Mulazid (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2025)
Abstract. This study conducts a systematic review to map the research landscape on alternative social protection policies in Indonesia from 2020 to 2025. It aims to identify thematic trends, methodological biases, and critical gaps in the literature, with a specific focus on resilience, digitalization, and governance. Adhering to the PRISMA protocol, we selected and rigorously analyzed 33 articles from Q1-Q4 indexed journals in the Scopus database, employing structured analytical frameworks for thematic synthesis and classification. Our findings reveal a significant paradigm shift towards Adaptive Social Protection (ASP) for responding to climate and economic shocks, alongside a dual narrative of optimism and risk concerning digital transformation. The analysis further uncovers a strong dominance of quantitative approaches, which we argue often obscures the nuanced realities of vulnerable groups, particularly regarding gendered impacts and digital inclusion. The discussion critically highlights a troubling disconnect between macro-level, technocratic evaluations and local-level dynamics, coupled with a general paucity of robust theoretical foundations in existing studies. We conclude that the field requires a reoriented future research agenda to critically interrogate the digital governance of social protection, systematically integrate intersectional perspectives, operationalize adaptive financing mechanisms, and unpack the societal 'black box' of policy implementation. The central implication is that building a resilient social protection system in Indonesia necessitates an interdisciplinary approach that deliberately bridges quantitative metrics with the qualitative lived experiences of marginalized populations. Keyword: Adaptive Social Protection, Digitalization, Governance, Intersectionality, Resilience. Abstrak. Studi ini menyusun tinjauan sistematis untuk memetakan lanskap penelitian kebijakan perlindungan sosial alternatif di Indonesia periode 2020-2025. Ini bertujuan mengidentifikasi tren tematik, bias metodologis, dan celah kritis dalam literatur, dengan fokus pada resiliensi, digitalisasi, dan tata kelola. Penelitian ini mengadopsi protokol PRISMA untuk menyeleksi 33 artikel terindeks Q1-Q4 dari database Scopus, yang kemudian dianalisis secara tematik dan diklasifikasikan menggunakan kerangka analitik terstruktur. Temuan utama mengungkap pergeseran paradigma menuju Perlindungan Sosial Adaptif (PSA) yang merespons guncangan iklim dan ekonomi, serta optimisme dan risiko dalam transformasi digital. Analisis kami menunjukkan dominasi pendekatan kuantitatif yang kuat, namun justru mengaburkan realitas lapangan kelompok rentan, seperti dampak kebijakan terhadap gender dan inklusi digital. Diskusi kami menekankan disonnect antara evaluasi makro-teknokratis dengan dinamika lokal, serta minimnya fondasi teoretis dalam studi-studi yang ada. Kesimpulannya, bidang ini memerlukan reorientasi agenda penelitian ke depan untuk mengkritisi aspek tata kelola digital, mengintegrasikan perspektif interseksional, mengeksplorasi pembiayaan adaptif, dan membuka 'kotak hitam' mekanisme sosial dalam implementasi kebijakan. Implikasinya, membangun sistem perlindungan sosial yang tangguh di Indonesia memerlukan pendekatan interdisipliner yang menjembatani metrik kuantitatif dengan pengalaman kualitatif masyarakat rentan. Keyword: Perlindungan Sosial Adaptif, Digitalisasi, Tata Kelola, Interseksionalitas, Resiliensi.